Implementasi Pemahaman Radiografer terhadap Exposure Index dalam Optimasi Prosedur Pemeriksaan Radiografi Computed Radiography - Irsal, Muhammad; Winarno, Guntur; Sutoro, Shinta Gunawati (Poltekkes Kemenkes Semarang, 2024)
Background: Increasing the exposure factor is often carried out by radiographers to reduce noise and maintain image quality in computer radiography (CR). Therefore, there is a need for awareness and understanding of the exposure index (EI) to implement optimization procedures in radiographic examinations. Methods: The research method is descriptive and analytical by providing questionnaires to radiographers in PA chest radiographic examinations. This research was carried out at hospitals A, B, and C in the Jakarta-Bogor area with the research carried out between August – October 2023. Statistical analysis used SPSS 27 with data coding previously. After that, the data is processed with descriptive statistics to determine the frequency, distribution, percentage, average, and standard deviation. Then, the test chi-square to determine the relationship between gender, age, education, and work experience in understanding CR optimization procedures. Next, to find out the relationship between age and weight and EI, a test was carried out by Pearson test to determine the level of relationship between the two variablesResults: was found that the level of awareness and understanding of radiographers regarding optimization procedures using EI is still low. Test results chi-square age-understanding 0.309, gender-understanding 0.772, education-understanding 0.036, experience-understanding 0.201. next are the test results Pearson for Hospital-A: age-EI 0.09, weight-EI -0.49, Hospital-B: age-EI -0.21, weight-EI 0.06, Hospital-C: age-EI -0.37, weight-EI 0.56. Conclusions: implementing EI in the optimization procedure, it needs to be confirmed by measuring the patient's radiation dose so that there are no errors in implementing the optimization.